2007
DOI: 10.1002/jor.20342
|View full text |Cite
|
Sign up to set email alerts
|

Murine model of prosthesis failure for the long‐term study of aseptic loosening

Abstract: We examined a novel mouse model of wear debris-induced prosthesis instability and osteolysis, and its application for the evaluation of therapy. A stainless steel or titanium-alloy pin was implanted into the proximal tibia to form a contiguous surface with the articular cartilage. In some mice, titanium particles were injected into the tibial canal during the surgery, followed by monthly intraarticular injection. MicroCT scans revealed that the implants without particle challenge were stable without bone miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 37 publications
(45 reference statements)
5
73
0
Order By: Relevance
“…Recently, studies of tissues harvested from revised joint replacements reported that proinflammatory M1 factors were predominant over M2 anti-inflammatory molecules (51)(52)(53)(54). Moreover, Rao et al (55) reported that IL-4, an M2 macrophage activator, mitigated polyethylene particle-induced osteolysis through macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies of tissues harvested from revised joint replacements reported that proinflammatory M1 factors were predominant over M2 anti-inflammatory molecules (51)(52)(53)(54). Moreover, Rao et al (55) reported that IL-4, an M2 macrophage activator, mitigated polyethylene particle-induced osteolysis through macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…However, this can be judged as a preliminary study, as no bone loss has been quantitatively proved (polystyrene particles used), only a few animals were included, the exact number of particles delivered could only be grossly extrapolated, and-surprisingly-no particles were observed on any histological bone section. We consider that major improvements were provided by Yang et al [48] and Zhang et al [49]. These authors used an effective long-term implant (pin implanted into proximal tibia to form a contiguous surface with the articular cartilage); an implant that stays well fixed after six months without particle challenge; monthly intra-articular injections for six months to achieve a long-term course (chronic reaction); pull-out tests as additional outcome measure; and most of all, in vivo gene transfer (using adenoassociated virus) to improve the delivery system of OPG-related therapy.…”
Section: Respective Discussionmentioning
confidence: 99%
“…This occurs largely due to the release of pro-inflammatory immune modulators such as IL-1a and b, IL-6, IL-18, and TNFa. [8][9][10][11][12][13][14] The NOD-like receptor protein, NALP3, located in the cytosol of macrophages, initiates the cleavage of pro-IL-1b into its mature, secreted form, IL-1b effectively triggering IL-1-associated inflammatory cascades. 13 Once these microdebris wear particles are phagocytized by macrophages, they release the above mentioned cytokines to attract and recruit more phagocytes that will release more chemotaxins which, in turn, perpetuates a positive feedback cycle of inflammation activation.…”
Section: Pathophysiologymentioning
confidence: 99%
“…As has been demonstrated in the literature, IL-1b has been intimately linked to osteolysis; to the extent of being used a secondary measure of periprosthetic bone resorption in several studies. [8][9][10][11][12][13][14][15]17,57,74,75 The activation of cytokine released by uric acid crystals in gout is similar to wear-debris particles activation an immune response in the setting of aseptic loosening, and therefore lies the potential benefit of these pharmacologics in periprosthetic osteolysis. A recent study has also REVIEW OF PERIPROSTHETIC OSTEOLYSIS proposed that the prophylactic administration of erythromycin may maximize the longevity of a prosthetic joint by lessening, or at least delaying, the effects of osteolysis immediately adjacent to the implanted construct.…”
Section: Medicationsmentioning
confidence: 99%